1987
DOI: 10.1002/ijc.2910390206
|View full text |Cite
|
Sign up to set email alerts
|

Non‐hodgkin's lymphoma and farming: An expanded case‐control study

Abstract: A previously published case-control study of agricultural risk factors involved male cases of non-Hodgkin's lymphoma registered under code 202 of the International Classification of Diseases (ICD). This study has been expanded with the inclusion of cases registered under ICD code 200, and additional controls. The expanded study comprises 100 ICD 200 cases and 83 ICD 202 cases registered during the period 1977-81, together with 338 controls selected from other cancer registrations during the same period. The la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 29 publications
5
66
0
Order By: Relevance
“…An excess risk of malignant lymphoma seen among agricultural workers in many countries has been related to the widespread occurrence of bovine leukaemia virus causing lymphosarcoma in cattle (Pearce et al, 1987). The milk of naturally infected cows frequently contains such infectious virus, and human cells can be infected in vitro (Ferrer et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…An excess risk of malignant lymphoma seen among agricultural workers in many countries has been related to the widespread occurrence of bovine leukaemia virus causing lymphosarcoma in cattle (Pearce et al, 1987). The milk of naturally infected cows frequently contains such infectious virus, and human cells can be infected in vitro (Ferrer et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, no significant associations were reported with potential exposure to phenoxy herbicides (OR 5 1.0, 90% CI: 0.7-1.5) or chlorophenols (OR 5 1.4, 90% CI: 0.8-2.3) in a New Zealand study. 147 In contrast, a Swedish case-control study 117 reported significant positive associations with selfreported exposure to phenoxy herbicides (OR 5 5.2, 95% CI: 1.6-17.0) and chlorophenols (OR for high-grade NHL 5 9.0, 95% CI: 2.9-28.0; OR for low-grade NHL 5 2.8, 95% CI: 1.2-6.5). In a later case-control study with many more cases, the same author reported non-significant associations with phenoxy herbicides (OR 5 1.5, 95% CI: 0.9-2.4) and chlorophenols (OR 5 1.1, 95% CI: 0.7-1.8).…”
Section: Occupational and Environmental Factors Occupational And Envimentioning
confidence: 92%
“…Pearce et al reported a significantly increased risk of NHL among abattoir workers (OR 5 1.8, 90% CI: 1.2-2.6) 627 but not tannery workers (OR 5 0.5, 90% CI: 0.1-1.8). 86 Tatham et al 71 found no excess risk of overall NHL among persons reporting meat packaging/processing occupations (OR 5 1.00, 95% CI: 0.72-1.40), whereas risk of follicular lymphoma was increased following over 2 years of employment in meat packaging or processing (OR 5 2.10, 95% CI: 1.10-4.20); however, there was no trend based on time since first exposure. A proportionate mortality study of white male members of a meat-cutters' union in Baltimore reported a mortality deficit of lymphosarcoma and reticulosarcoma (PMR 5 0.61).…”
Section: Interactions With Environment and Lifestyle Factorsmentioning
confidence: 97%
“…Conversely, HCB was assessed in 8 of these studies, 46,48,54,55,58,60,126,127 of which only one observed an association. b-Hexachlorocyclohexane concentrations were positively associated with NHL in only 2 52,123 of the 6 studies that measured it in either plasma, serum, or adipose tissue. Dieldrin levels were assayed in 4 studies, 54,58,60,126 with only one 54 finding evidence of a positive association with NHL.…”
Section: Prostate Cancermentioning
confidence: 97%
“…121 In Nebraska, a nonsignificant 50% excess risk of NHL was observed among users of 2,4-D, but the risk did increase to over 3-fold for those who used the herbicide 20 or more days per year. 122 Little evidence of an association between phenoxy acid herbicides and NHL was observed in New Zealand, 123 Washington state, 62 or Minnesota and Iowa. 124 A meta-analysis of 13 case-control studies published between 1993 and 2005 observed an overall significant meta-OR between occupational exposure to pesticides and NHL (OR, 1.35; 95% CI, 1.2-1.5).…”
Section: Prostate Cancermentioning
confidence: 99%